Improved search methods for assessing Delay-Tolerant Networks vulnerability to colluding strong heterogeneous attacks. (1st September 2017) - Bucur, Doina; Iacca, Giovanni
Highlights: Blackhole fast-moving attackers are effective against the First-Contact protocol. Flooding fast-moving attackers are effective against the Epidemic protocol. Mixed blackhole and flooding are effective against the Spray-and-Wait protocol. MaxProp is resilient; flooding attackers will mildly affect the protocol. Abstract: Increasingly more digital communication is routed among wireless, mobile computers over ad-hoc, unsecured communication channels. In this paper, we design two stochastic search algorithms (a greedy heuristic, and an evolutionary algorithm) which automatically search for strong insider attack methods against a given ad-hoc, delay-tolerant communication protocol, and thus expose its weaknesses. To assess their performance, we apply the two algorithms to two simulated, large-scale mobile scenarios (of different route morphology) with 200 nodes having free range of movement. We investigate a choice of two standard attack strategies (dropping messages and flooding the network), and four delay-tolerant routing protocols: First Contact, Epidemic, Spray and Wait, and MaxProp. We find dramatic drops in performance: replicative protocols (Epidemic, Spray and Wait, MaxProp), formerly deemed resilient, are compromised to different degrees (delivery rates between 24% and 87%), while a forwarding protocol (First Contact) is shown to drop delivery rates to under 5% — in all cases by well-crafted attack strategies and with an attacker group of size less than 10% the total network size. Overall, we show that the two proposed methods combined constitute an effective means to discover (at design-time) and raise awareness about the weaknesses and strengths of existing ad-hoc, delay-tolerant communication protocols against potential malicious cyber-attacks.